1989
DOI: 10.1042/bj2600863
|View full text |Cite
|
Sign up to set email alerts
|

Haem-binding-site heterogeneity and haem Cotton effects of Glycera dibranchiata monomeric haemoglobins

Abstract: The five major components of the monomeric haemoglobin from Glycera dibranchiata were separated and characterized by absorption spectroscopy, isoelectric focusing, azide-binding affinities and nitrosyl autoreduction kinetics. The differences found among the components are discussed in terms of haem-pocket variations. In addition, the Fourier-transform i.r. spectra of pooled monomeric haemoglobin carbonyl (HbmCO) and the major component carbonyl are reported. The c.d. spectra of the carbonyl and azide derivativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

1990
1990
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…The observed splitting of the a band in the spectrum of MbmNO has been attributed to nondegeneracy of the eg(ir*x->,) orbitals of the porphyrin resulting from dxz, dyz nondegeneracy traced to the stereochemical influence of the distal histidine. [13][14][15] The absence of splitting in the a band of the HbcmNO spectrum is consistent with the absence of a distal histidine in this hemoglobin. A similar, though less pronounced splitting is seen for MbnCO, again in contrast with the HbcnCO analogue.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…The observed splitting of the a band in the spectrum of MbmNO has been attributed to nondegeneracy of the eg(ir*x->,) orbitals of the porphyrin resulting from dxz, dyz nondegeneracy traced to the stereochemical influence of the distal histidine. [13][14][15] The absence of splitting in the a band of the HbcmNO spectrum is consistent with the absence of a distal histidine in this hemoglobin. A similar, though less pronounced splitting is seen for MbnCO, again in contrast with the HbcnCO analogue.…”
supporting
confidence: 77%
“…Contrary to previous indications,26 recent work27 has shown that in native-heme Mb (yellowfin tuna) the precise value of the heme orientational equilibrium constant is dependent to unequivocally that the dominant heme orientations are the same as those of their other derivatives, including the aquamet proteins precursory to the iron(III) nitrosyls. 15 In order to account for the different band shapes among the above derivatives, the rate of any ligand-dependent heme reorientation would need to be fast relative to the time required to prepare an adduct and obtain its optical spectrum. This seems unlikely: when horse heart myoglobin is reconstituted15,28 from apoprotein by using Fe(CO)-(PPIX) at pH 7 (µ = 0.2 phosphate, 1 atm CO, 20 °C), the subsequent equilibrative reordering of the heme from its initially randomized orientational distribution may be followed by circular dichroism spectroscopy and is observed to occur with a first-order rate constant of only (3.9 ± 0.2) X 10~7 s"1.…”
mentioning
confidence: 99%